2017
DOI: 10.1080/00016357.2017.1356467
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the salivary urea and creatinine tests as screening methods of chronic kidney disease in Vietnamese patients

Abstract: Both salivary urea and creatinine have a high capacity for serum creatinine estimation. Salivary urea and creatinine tests can be used as low-cost, easily accessible and noninvasive tools for screening, diagnosing, monitoring treatment outcomes and ascertaining prognosis of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
3
16
0
1
Order By: Relevance
“…Our study showed that salivary urea and creatinine concentrations were significantly higher in CKD dogs compared with healthy subjects. These results are in agreement with previous studies made in humans where high values of salivary urea and creatinine were observed in patients with CKD [11,17,18]. An explanation for these findings is that in CKD the kidneys can not excrete creatinine and urea, and therefore their blood concentrations increase leading to the diffusion of these compounds to saliva [19].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that salivary urea and creatinine concentrations were significantly higher in CKD dogs compared with healthy subjects. These results are in agreement with previous studies made in humans where high values of salivary urea and creatinine were observed in patients with CKD [11,17,18]. An explanation for these findings is that in CKD the kidneys can not excrete creatinine and urea, and therefore their blood concentrations increase leading to the diffusion of these compounds to saliva [19].…”
Section: Discussionsupporting
confidence: 93%
“…Regardless of the mechanism(s) accounting for the abundance of phosphorus in saliva, the evidence of a correlation between saliva phosphorus and plasma phosphorus could be explained hypothesizing that plasma phosphorus controls the secretion and/or the diffusion of phosphorus in saliva. With regard to urea, its saliva concentrations were almost identical and highly correlated with plasma urea in accordance with previous observations . The high‐order correlation of saliva urea with plasma urea and the identity of urea concentrations in plasma and saliva reasonably reflected the chemical characteristics of urea, that is, extremely soluble and diffusive.…”
Section: Discussionmentioning
confidence: 99%
“…An important prerequisite for the use of saliva in diagnostic workup is that the salivary levels of the marker associated with a given disorder should mirror the profile of the marker in biological samples used as gold standard in medical practice. Previous observations indicated that correlations between plasma concentrations and saliva concentrations are detectable for some but not for all analytes . It is well established that small molecules as phosphorus and urea are measurable in saliva .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations